Analysis of Reliability and Security of Smart Grid Network Communication System in the Implementation of Renewable Energy Source Integration - Ilham Hardiansyah Y. S; Parlin Siagian; Rahmaniar, Rahmaniar (Jurnal Scientia, 2024)
Smart Grid System are key to integrating renewable energy sources into existing power grids. This article analyzes two critical aspects of a Smart Grid system: communication reliability and security. Reliability of communication systems is essential to ensure timely and accurate data delivery between various entities in the network. Meanwhile, communication system security is a crucial factor in protecting infrastructure from cyberattacks that can disrupt the overall system's operation. This study conducts an in-depth evaluation of the technologies used in Smart Grid systems, as well as a review of the challenges and solutions in ensuring the reliability and security of communication systems in the context of renewable energy integration. The results of this analysis provide valuable insights for the development and implementation of more efficient and reliable Smart Grid systems in the future.